An Analysis Of Students’ Speaking Anxiety - Ambawani, suprih; Putranti, Bernadetta Eko; Saudah, Siti (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The research aims to investigate the students’ speaking anxiety level and factors that contribute to the students’ speaking anxiety in first-semester students of Vocational Program of Industrial and Mechanical Technology of Institut Sains & Teknologi AKPRIND Yogyakarta. This research is descriptive qualitative. There are 13 participants involved in this research. To obtain data, FLCAS questionnaires and interviews are used. The result shows that there are 7 students (53.84 %) who are categorized as anxious students, 4 students (30.77%) are categorized as mildly anxious students and only 2 students (15.38 %) are categorized as relaxed students. It is also revealed that the dominant type of factor contributing to students' speaking anxiety is communication apprehension, followed by test anxiety. Negative evaluations do not influence the students’ anxiety in speaking.